2013
DOI: 10.1039/c3ra40486b
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the chemistry of biomass pyrolysis by means of tunable synchrotron photoionisation-mass spectrometry

Abstract: Imaging'' biomass conversion: pyrolysis is the first reaction involved in all thermal processes for biofuels and green chemicals production. Synchrotron light ionisation and mass spectrometry is used for the first time to investigate biomass pyrolysis. The soft and tunable ionisation source coupled with ab initio calculations reveals chemical mechanisms and new major intermediate species. This methodology could be extended to the thermal and catalytic conversion of all other materials. Primary volatile product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 60 publications
2
67
1
Order By: Relevance
“…Williams et al [33] suggested that biomass with a high content of lignin may form larger soot fractions due to its ability to generate phenolic tars. A significant fraction of aromatic tars and soot originates from lignin pyrolysis, mainly composed of guaiacol and syringol-type units [34][35][36]. Ross et al [37] stated that wood soot contains PAH material, promoted by the presence of acetylene at higher temperatures.…”
Section: The Solid Product Yieldmentioning
confidence: 99%
“…Williams et al [33] suggested that biomass with a high content of lignin may form larger soot fractions due to its ability to generate phenolic tars. A significant fraction of aromatic tars and soot originates from lignin pyrolysis, mainly composed of guaiacol and syringol-type units [34][35][36]. Ross et al [37] stated that wood soot contains PAH material, promoted by the presence of acetylene at higher temperatures.…”
Section: The Solid Product Yieldmentioning
confidence: 99%
“…The aim of this work is to deeply understand these reactions under conditions representative of biomass gasification in air-blown fluidized beds, but also PAH formation in wood combustion furnaces [9]. A significant fraction of aromatic tars and soot originates from lignin pyrolysis products mainly composed of guaiacol-type and syringol-type units [5], [10], [11] and [12]. Carbohydrates from cellulose and hemicellulose can also contribute to aromatic formation through the production of light unsaturated species such as acetylene and propargyl radicals [5], [13] and [14].…”
Section: Introductionmentioning
confidence: 99%
“…3(b) [50,53,64]. More extensive sequential depolymerization reactions dominate in the temperature rangẽ 300-400°C, resulting primarily in the formation of levoglucosan (1, 6-anhydro-beta-d-glucopyranose), a dehydrated analogue of glucose, and other primary anhydrosugars and oligosaccharides [67]. Yields of up to around 60 wt% levoglucosan have been reported [59].…”
Section: Chemistry Involved In Thermo-chemical Conversionmentioning
confidence: 99%